THE INFLUENCE OF MULTIMEDIA BASED INQUIRY TRAINING LEARNING MODEL ON STUDENT’S ACHIEVEMENT ON MOMENTUM AND IMPULSE IN CLASS XI SMA N 1 PERBAUNGAN YEAR 2013/2014 - Jefri S Waruwu; Motlan . (UNIVERSITAS NEGERI MEDAN, 2014)
ABSTRACT Physics is one of the core curricullum of high school in Indonesia. It studies about natural phenomena. Howefer student’s achievement on high school physics in Indonesia is still relatively low. This is possibility due to the lack of learning and teaching aproaches. The objective of research is to know the influence multimedia based inquiry training learning model on student’s achievement on momentum and impulse in class XI, SMA N 1 Perbaungan, year 2013/2014”. Based on the research find from the analysis of result it can conclude that it has the effect of inquiry training learning model on student’s achievement on momentum and impulse in class XI SMA N 1 Perbaungan, year 2013/2014. It means inquiry training learning model better than conventional model to increase of student achievement. Key Word: influence of multimedia based inquiry training learning model, student achievement, activity.